Protecting People: Promoting Digital Consumer Rights - Ira Aprilianti (Center for Indonesian Policy Studies (CIPS), 2020)
Between 2015-2019, the size of Indonesia's internet economy has quadrupled and now cuts across various sectors of the economy. On issues of consumer rights and protections, regulators have struggled to keep up with this rapid growth. What is needed is a clear regulatory framework and consensus on the role of the government within the digital economy in order find balance between growth and digital innovations and ensuring consumer protection. CIPS' Protecting People: Promoting Digital Consumer Rights Policy Paper outlines the growing of Indonesia's digital economy, challenges surrounding the protection of consumer rights in the digital space, and the existing regulatory and institutional frameworks to ensure consumer protection. This policy paper also presents seven policy recommendations for Indonesian policymakers that aim to strengthen the regulatory and institutional framework for consumer protection without sacrificing potential growth of Indonesia's digital economy.
Keywords: 330